Value of bacteria in our dairy products - Secrest, Jacob Ulrich (My University, 1894)
Introduction: Whenever they hear the word “bacteria” most people are apt to shudder with horror, and look upon them as the sworn enemy of the human race. We have a sort of a shrinking when anyone speaks of the number of bacteria in the mill or water we are drinking. The reason for this is evident. After bacteria were discovered the first question of importance associated with them was their close relation to the causes of many terrible diseases and epidemics that swept away the population of whole communities. Scientists then began to investigate these microscopic organisms and soon established what is now known as the “Germ Theory of Disease”. With their minds intent upon this side of the question they did not pay much attention to the good that bacteria might do in the world. The part they played in disease was a more interesting study. The consequences were that these investigations and studies was to impressed on the minds of the people the great harm done by these invisible pests.
Citation: Secrest, Jacob Ulrich. Value of bacteria in our dairy products. Senior thesis, Kansas State Agricultural College, 1894.
Morse Department of Special Collections
Keywords: Bacteria; Dairy; Bacteriology; Theses; Manuscripts (documents)